Analisis Perubahan Daya Motor Pada Pompa Sweet Water Di PT. Unilever Oleochemical Indonesia - Putra, Hadi Wiranata; Dalimunthe, Muhammad Erpandi; Tharo, Zuraidah (Politeknik Harapan Bersama Tegal, 2025)
The three-phase induction motor stands as the predominant choice in industrial applications due to its numerous benefits. To optimize its performance, maintaining the integrity of the motor's power supply is essential. A significant factor influencing power quality is the load applied to the motor. This research focuses on analyzing and calculating the power consumption of a three-phase induction motor under varying control valve opening conditions, ranging from 10% to 100%. The motor under study operates as a pump driver, facilitating the transfer of sweet water in the fatty acid production facility at PT Unilever Oleochemical Indonesia. Key parameters examined include variations in current, power factor, and input power. Findings indicate that when the valve opening varies from 10% to 100%, the motor’s power output reaches up to 106% of its rated capacity at full valve opening. Conversely, at the minimum valve opening, the motor’s efficiency drops to 67.9% relative to its nominal power.